COVID-19 Vaccination and Fear Indices Impacting on Healthcare Stock Indices Price in Southeast Asia during the Vaccination Rollout - Jeremiah, Matthew; Setiadi, Andreas; Havidz, Shinta Amalina Hazrati (Organizations and Markets in Emerging Economies, 2023)
This research aims to investigate the impact of COVID-19 vaccinations and fear indices on healthcare stock index prices in Southeast Asia during the vaccination rollout. The authors analyzed four Southeast Asian countries (i. e., Indonesia, Malaysia, Singapore, and Thailand) during the period of vaccination rollout by using daily weekday data from 1 March to 19 November 2021, with a total of 760 observations. The authors utilized Feasible Generalized Least Squares (FGLS) for the main methodology and incorporated Generalized Method of Moments (GMM) as the robustness check. The authors discovered three findings, including: (1) Increased number of people exploring news around vaccine doses created positive sentiments, while vaccine hesitancy revealed the opposite result; (2) Healthcare stock was found to be a defensive sector during the later period of the COVID-19 pandemic; (3) Many new investors arose during the pandemic, and it led to herding behavior thus, the investors’ decision-making was based on sentiment. It concludes that vaccine dose and hesitancy news can be utilized to manage investors’ portfolio investment in the healthcare sector. The government should disseminate more about the COVID-19 vaccination to citizens to prevent vaccine hesitancy. Investors could consider including healthcare stock in their portfolios to minimize risk during a pandemic. Citizens’ wise usage of social media and cooperation are needed to end the pandemic.